Anti-advanced glycation end-products and antibacterial inhibitory activities of Neonauclea formicaria (Rubiaceae) - Layug, Mirakel Zoe P.; Domagas, Jose Nathaniel F.; Supan, Enrico C.; Cuevas, Cameron D.; Benitez, Ray Allen L.; Ordas, Jorge Anton D.; Tan, Mario A. (Journal of Phytology, 2025)
Neonauclea species have been studied for their phytochemical and potential pharmacological uses. However, many of its species still remained unexplored. The Philippine endemic Neonauclea formicaria has been documented for its ethnobotanical use, but little has been reported on its phytochemical and pharmacological profile. Hence, this study evaluates the total phenolic (TPC) and flavonoid (TFC) contents and assesses its ethanolic leaf extracts’ antiglycation, antioxidant, and antibacterial activities. N. formicaria leaf extracts at 1000 ppm gave 63.02±5.82 mg GAE/g DW TPC and 31.25±4.24 mg QE/g DW TFC. The extract showed a concentration-dependent activity in inhibiting AGE formation for the antiglycation assay, with an IC50 value of 2823.5 ppm. In antioxidant assay, the extract exhibited the highest TEAC value of 419.5±14.3 mg TE/kg DW at 250 ppm. Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa were shown to be the most susceptible to the leaf extract (1000 ppm), with zones of inhibition at 16.56±5.65 mm and 14.06±2.65 mm, respectively. The results highlight that N. formicaria bears promising properties with pharmacological and nutraceutical applications.